Potassium Imbalance Leading to Arrhythmias in Patients Undergoing Cardiac Surgery on Cardiopulmonary Bypass - Muhammad Saeed Afridi, Muhammad Suleman Khan, Sohail Rashid, Zain Mehmood Butt, Rimsha Tauqeer, Mattiur Rahman, Ashiqullah Arman, Iqra Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of factors that cause potassium imbalance in patients with postoperative arrhythmias after cardiac Bypass surgery Material and methods: During the time period of 2 November 2018 through 10 January 2020, 100 patients with heart disease receiving open-heart surgery were enrolled in a prospective observational research conducted by the cardiac surgery department at the Punjab Institute of Cardiology in Lahore. Both genders of age 17-70 years were included and patients with cyanotic heart disease congenital heart disease, previous cardiac surgery and urgent CABG were excluded. Results: Our results showed that of 100 patients, 59 (59%) were male and 41 (41%) were female and the mean age was14.243 ± 50.12 years. 6 patients had preexisting renal failure and 9 had postoperative renal failure. Overall potassium imbalance was noted in 39 patients, 33 were hypokalemic and 6 were hyperkalemic and the mean potassium with S.D was 3.95±0.83 and 37 had postoperative arrhythmias out of which 18 (54.5%) were hypokalemic and 2 (33.3%) were hyperkalemic. Preoperative drugs, preexisting renal failure, CPB time, aortic cross clamp time, intraoperative potassium levels, time on ventilation, postoperative urine output, potassium infusion, postoperative renal failure, arrhythmias and total hospital stay were found to be statistically significant. Conclusion: Potassium imbalance post-cardiopulmonary bypass is major factor that may lead to increased risk of postoperative arrhythmias. Keywords: Potassium imbalance, cardiopulmonary bypass, postoperative arrhythmias, renal failure, hypokalemia